DYNAMICS OF CHANGES IN CYTOKINE LEVELS IN PATIENTS WITH DIABETIC FOOT SYNDROME UNDER VARIOUS TYPES OF ANESTHESIA - Khamdamov Bakhtiyor Zarifovich; Oltiev Usmon Bebitovich; Khamdamov Alisher Bakhtiyorovich; Usmonov Amirbek Usmonovich (Web of Journals Publishing, 2024)
Objective: comparative study of the effect of general, epidural and conduction anesthesia on the level of cytokines in patients with diabetic foot syndrome.
Keywords: diabetic foot syndrome, anesthesia, cytokines.